Awareness of statin–food interactions using grapefruit as an example: a cross-sectional study in Eastern Province of Saudi Arabia - Baraka, Mohamed A.; Elnaem, Mohamed Hassan Abdelaziz; Elkalmi, Ramadan; Sadeq, Adel; Elnour, Asim Ahmed; Chacko, Royes Joseph; AlQarross, Abdullah H.; Moustafa, Mahmoud M. AbdRabo (Oxford University Press, 2021)
Abstract Objectives The purpose of this study is to assess patients’ knowledge regarding statin–grapefruit interactions, to identify any pertinent demographic characteristics that may influence knowledge of this drug–food interaction, and to identify preferred patient sources of health information.